SFRP2 affects prenatal muscle development and is regulated by microRNA-1/206 in pigs - Yan-jiao MA; Ya-lan YANG; Wei SUN; Rong ZHOU; Kui LI; Zhong-lin TANG (Journal of Integrative Agriculture, 2016)
Secreted frizzled-related protein 2 (SFRP2), a member of the SFRPs family, is associated with cell growth and differentiation in myogenesis. Our previous study suggested that SFRP2 was a potential target of microRNA (miRNA)-1/206, which was considered as myomiRs. To further explore the biological function and regulation mechanisms of the SFRP2 gene in porcine skeletal muscle development, we first analyzed the sequence structure of the porcine SFRP2 gene. Subsequently, we detected its tissue distribution in adult Tongcheng pigs (a Chinese indigenous breed) and investigated its dynamic expression in developmental skeletal muscle (13 prenatal and 7 postnatal time points) in Tongcheng pigs. An interaction analysis between SFRP2 and myomiRs was also performed. The results showed that the expression pattern of the SFRP2 varied greatly across diverse tissues. It exhibited abundant expression in prenatal skeletal muscle and peaked at 55 days post coitus (E55), and had a lower expression in postnatal skeletal muscle, indicating that the SFRP2 gene might affect porcine embryonic skeletal muscle development. Co-expression analysis revealed that the expression levels of SFRP2 correlated negatively with miRNA-1 (r=–0.570, P-value=0.009) and miRNA-206 (r=–0.546, P-value=0.013), but positively with SFRP1 (r=0.613, P-value=0.004). The bioinformatics analysis and dual luciferase assay verified that the SFRP2 was a putative target of miRNA-1/206 in pigs. Therefore, this study is helpful for understanding the biological function and molecular regulation of the SFRP2 gene during porcine skeletal muscle development.